2018
DOI: 10.1680/jadcr.17.00120
|View full text |Cite
|
Sign up to set email alerts
|

Chemical aspects related to using recycled geopolymers as aggregates

Abstract: Despite extensive research into sustainability of geopolymers, end-of-life aspects have been largely overlooked. A recycling scenario is examined in this study. This requires an investigation of alkali leaching potential from a geopolymeric matrix. To study the feasibility of geopolymer cement (GPC) recycling, the migration of alkalis was evaluated for the first time on a microstructural level through energy dispersive X-ray (EDX) scanning electron microscopy (SEM) elemental mapping and leaching tests. Macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has also been identified that there is a strong need for more refined and updated life-cycle inventory data for activator constituents including sodium silicate [303,305,313], as the currently available international databases do not reflect current production practice or processes. The assessment of recyclability [314,315] and release of potentially problematic elements (toxic or naturally occurring radioactive materials) [316][317][318] from AAMs in service has also received some attention as an essential constituent of a full cradle-to-grave or cradle-to-cradle environmental assessment. This will doubtless gain further importance as noncarbon emissions become more of a focus in material and product assessments worldwide, while the sources and characteristics of waste materials used in AAM production become ever more diverse.…”
Section: Lca and Environmental Aspectsmentioning
confidence: 99%
“…It has also been identified that there is a strong need for more refined and updated life-cycle inventory data for activator constituents including sodium silicate [303,305,313], as the currently available international databases do not reflect current production practice or processes. The assessment of recyclability [314,315] and release of potentially problematic elements (toxic or naturally occurring radioactive materials) [316][317][318] from AAMs in service has also received some attention as an essential constituent of a full cradle-to-grave or cradle-to-cradle environmental assessment. This will doubtless gain further importance as noncarbon emissions become more of a focus in material and product assessments worldwide, while the sources and characteristics of waste materials used in AAM production become ever more diverse.…”
Section: Lca and Environmental Aspectsmentioning
confidence: 99%